2011
DOI: 10.1007/s10337-011-2094-3
|View full text |Cite
|
Sign up to set email alerts
|

New Grafted Nanosilica-Based Sorbent for Needle Trap Extraction of Polycyclic Aromatic Hydrocarbons from Water Samples Followed by GC/MS

Abstract: In this work, the preparation of a new grafted nanosilica-based sorbent was extensively investigated. An inexpensive modifier, cis-9-octadecenoic acid (oleic acid) was selected to be grafted on the surface of the nanosilica particles as the support. The grafting process was accurately confirmed by Fourier transform infra-red spectrometry (FT-IR). Applicability of the prepared sorbent was thoroughly examined by needle trap extraction (NTE) method. The grafted sorbent was dispersed in the appropriate solvent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, the use of nanosilica for extraction of organic pollutants is rather inconsiderable. To overcome this problem, nanosilica particles must be grafted with an organic modifier . The PZC of SiO 2 is about 2–3, as reported in the literature; therefore, silica nanoparticles are negatively charged at higher and nutrient pH, and consequently, their dispersions in various water and biological media would be stable.…”
Section: Mechanisms and Properties Of Nanomaterials As Adsorbentsmentioning
confidence: 99%
“…Thus, the use of nanosilica for extraction of organic pollutants is rather inconsiderable. To overcome this problem, nanosilica particles must be grafted with an organic modifier . The PZC of SiO 2 is about 2–3, as reported in the literature; therefore, silica nanoparticles are negatively charged at higher and nutrient pH, and consequently, their dispersions in various water and biological media would be stable.…”
Section: Mechanisms and Properties Of Nanomaterials As Adsorbentsmentioning
confidence: 99%
“…It was reported that the heating temperature is a key parameter influencing the extraction efficiency in the NTD method (Bagheri et al , ). In this study, the peak numbers and areas were used as criterions to optimise extraction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the overall chromatographic performance in terms of peak intensity or peak capacity is significantly altered by increasing the temperatures, but the number of peaks extracted reaches a maximum at 70°C. It is worthy to note that high temperatures might increase desorption of analytes from the sorbents, resulting in the decrease of the amounts of compounds being retained by the NTD methods (De Crom et al, 2010;Bagheri et al, 2011b). A temperature of 70°C was thus chosen as the optimised extraction temperature in further experiments.…”
Section: Effect Of Sample Heating Temperaturementioning
confidence: 99%
“…Because of their high partition coefficients and low water solubilities, it is very important to develop a highly sensitive analytical method to detect them in natural and waste water [19].…”
Section: Introductionmentioning
confidence: 99%